1994
DOI: 10.3354/meps103111
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary pigments and organic carbon in relation to microalgal and benthic faunal abundance in the Gulf of Carpentaria

Abstract: Sediment samples were collected at 105 sites throughout the Gulf of Carpentaria, Australia, in November-December 1990. Highest concentrations of chlorophyll a in the sediment occurred in 3 regions: the southeast, the northeast and the western Gulf. Fucoxanthin, the pigment indicative of diatoms and pryrnnesiophytes, was present at most sites. Astaxanthin, present in microcrustaceans, was most highly concentrated in the same areas as chlorophyll a. The concentration of organic carbon was highest in the northwes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…On the other hand, the increase in pheophytin concentration is probably due to the eating of algae by zooplankton [41]. It was found that the degree of chlorophyll destruction depends on both the concentration of algae and the rate of their consumption and the type of consume [42]. The obtained pigment index values (E430/E664) from 3 to 5, indicate the predominance of heterotrophic metabolism over autotrophic in the photosynthetic community [6].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the increase in pheophytin concentration is probably due to the eating of algae by zooplankton [41]. It was found that the degree of chlorophyll destruction depends on both the concentration of algae and the rate of their consumption and the type of consume [42]. The obtained pigment index values (E430/E664) from 3 to 5, indicate the predominance of heterotrophic metabolism over autotrophic in the photosynthetic community [6].…”
Section: Discussionmentioning
confidence: 99%